Transplacental Innate Immune Training via Maternal Microbial Exposure: Role of XBP1-ERN1 Axis in Dendritic Cell Precursor Programming - Mincham, Kyle T.; Jones, Anya C.; Bodinier, Marie; Scott, Naomi M.; Lauzon-Joset, Jean-Francois; Stumbles, Philip A.; Bosco, Anthony; Holt, Patrick G.; Strickland, Deborah H. (Frontiers in Immunology, 2020)
We recently reported that offspring of mice treated during pregnancy with the microbial-derived immunomodulator OM-85 manifest striking resistance to allergic airways inflammation, and localized the potential treatment target to fetal conventional dendritic cell (cDC) progenitors. Here, we profile maternal OM-85 treatment-associated transcriptomic signatures in fetal bone marrow, and identify a series of immunometabolic pathways which provide essential metabolites for accelerated myelopoiesis. Additionally, the cDC progenitor compartment displayed treatment-associated activation of the XBP1-ERN1 signalling axis which has been shown to be crucial for tissue survival of cDC, particularly within the lungs. Our forerunner studies indicate uniquely rapid turnover of airway mucosal cDCs at baseline, with further large-scale upregulation of population dynamics during aeroallergen and/or pathogen challenge. We suggest that enhanced capacity for XBP1-ERN1-dependent cDC survival within the airway mucosal tissue microenvironment may be a crucial element of OM-85-mediated transplacental innate immune training which results in postnatal resistance to airway inflammatory disease.